2004
DOI: 10.1128/mcb.24.11.4994-5004.2004
|View full text |Cite
|
Sign up to set email alerts
|

The Nuclear Hormone Receptor Coactivator NRC Is a Pleiotropic Modulator Affecting Growth, Development, Apoptosis, Reproduction, and Wound Repair

Abstract: Nuclear hormone receptor coregulator (NRC) is a 2,063-amino-acid coregulator of nuclear hormone receptors and other transcription factors (e.g., c-Fos, c-Jun, and NF-B). We and others have generated C57BL/6-129S6 hybrid (C57/129) NRC ؉/؊ mice that appear outwardly normal and grow and reproduce. In contrast, homozygous deletion of the NRC gene is embryonic lethal. NRC ؊/؊ embryos are always smaller than NRC ؉/؉ embryos, and NRC ؊/؊ embryos die between 8.5 and 12.5 days postcoitus (dpc), suggesting that NRC has … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

5
87
0

Year Published

2006
2006
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 52 publications
(92 citation statements)
references
References 76 publications
(114 reference statements)
5
87
0
Order By: Relevance
“…We also found that apoptosis was increased and proliferation was decreased in the ASC-2 ϩ/Ϫ islets. The involvement of ASC-2 in the apoptotic process has been suggested previously by two other groups (35,43). ASC-2 Ϫ/Ϫ mouse embryo fibroblasts grow at a reduced rate and exhibit apoptosis.…”
Section: Discussionmentioning
confidence: 82%
See 2 more Smart Citations
“…We also found that apoptosis was increased and proliferation was decreased in the ASC-2 ϩ/Ϫ islets. The involvement of ASC-2 in the apoptotic process has been suggested previously by two other groups (35,43). ASC-2 Ϫ/Ϫ mouse embryo fibroblasts grow at a reduced rate and exhibit apoptosis.…”
Section: Discussionmentioning
confidence: 82%
“…ASC-2 Ϫ/Ϫ mouse embryo fibroblasts grow at a reduced rate and exhibit apoptosis. This apoptosis is inhibited by zVAD-fmk, an irreversible pancaspase inhibitor, suggesting a role for caspases in the apoptosis of ASC-2 Ϫ/Ϫ MEFs (35). The other group reported a slight increase of apoptosis in the terminal end buds of ASC-2-deficient mammary glands relative to wild-type mammary glands (43).…”
Section: Discussionmentioning
confidence: 93%
See 1 more Smart Citation
“…To establish potentially interrelated functions of ASC2 and MLL3/4, we have used a variety of in vitro and in vivo assays (8,19,30). Interestingly, our recent analysis of a homozygous mouse line that expresses an enzymatically inactivated mutant form of MLL3 demonstrated genetic interactions between ASC-2 and MLL3 (8,15). Therefore, and because these animals show only a partial embryonic lethality (8) as opposed to the early embryonic lethality of ASC-2-null mice (1), they serve as an excellent model system to study the physiological function of ASCOM.…”
Section: Targeted Inactivation Of Mll3 H3k4 Methyltransferase Activitmentioning
confidence: 99%
“…MLL3 ⌬/⌬ mice also show decreased white adipose tissue (WAT), as described here, and kidney ureter urothelium tumors (unpublished results) and resistance to high-fat diet-induced fatty liver formation (27). The early embryonic lethality of ASC-2-null mice (20)(21)(22)26) versus the milder phenotypes of MLL3 ⌬/⌬ mice, along with the demonstrated association of ASC-2 with MLL3 or MLL4 in ASCOM (5, 10) and the overlapping phenotypes of isogenic ASC-2 ϩ/Ϫ mice (26) and MLL3 ⌬/⌬ mice (10), suggest that many ASC-2-target genes are likely to be regulated by MLL3 and MLL4 in a redundant manner. Indeed, our recent results have shown that ASCOM-MLL3 and ASCOM-MLL4 appear to be redundant coactivators both for the tumor suppressor p53 (unpublished results) and the liver X receptor (LXR) and retinoic acid receptor (RAR) (10,27).…”
mentioning
confidence: 99%